Social Construction of Defecation Behavior in Disadvantaged Villages - Edy Agustinus; Resky Nanda Pranaka; Efriani Efriani (Jurnal Kesehatan Masyarakat, 2023)
In 2020, the status of the Disadvantaged Village is pinned to Bengawan Ampar Village. The sanitation achievement is only 31% which indicates that defecation behavior in the area needs better direction. This study was conducted from July to December 2020. Informants were determined by purposive sampling. There are 8 informants, 4 have latrines, and the rest do not. They are 29-59 years old. This qualitative research aims to analyze the social construction of defecation behavior in people in disadvantaged villages. By using the analysis of the Miles and Huberman model, the study results confirm that most of the defecation behavior of the people of Bengawan Ampar Village is in the river and yard. The contributing factors include (1) the old habit of defecating in the river or yard; (2) economic conditions; (3) pigs are not penned; (4) limited infrastructure such as water, electricity, and roads; (5) lack of counseling; and (6) limited number of health workers.